An Exploration of the Influence of Satirical Advertising on Building Brand Equity amongst South African Millennials - Sturmheit, Adam Tate (The IIE, 2019)
Due to the continuously increasing importance of differentiation in the marketplace, building a strong brand equity has become a crucial element of competition, and brands are constantly seeking unique methods of appealing to consumers. One available method is advertising utilising different form of humour and satirical humour in television advertising has become particularly popular in modern South African advertising.The contents of this research paper posits that satirical television advertising can be utilised as an effective brand equity building tactic. Furthermore; it is proven that satirical humour has a positive influence on numerous dimensions of brand equity including: brand awareness, brand associations and brand loyalty. With accurate and entertaining use of satire in television advertising a brand is effectively able to increase their brand appeal, brand perceptions and overall brand equity.
Keywords: Brand; Brand building; Brand equity; Advertising; Television advertising; Satirical television advertising; Brand loyalty